2022
DOI: 10.1186/s12905-022-01856-1
|View full text |Cite
|
Sign up to set email alerts
|

Contraceptive uptake and associated factors among women in the immediate postpartum period at Kawempe Hospital

Abstract: Introduction Within Africa, contraceptive use is low although about 214 million women who are not using contraception want to avoid pregnancy. In Uganda, modern contraceptive uptake is at 35% resulting in unwanted or unplanned pregnancies which may increase morbidity and mortality among children and mothers. Contraceptive uptake at 6 weeks postpartum is encouraged but it is not very effective since there is low attendance during this visit. Additionally, some women may have become sexually acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…The higher awareness of women who delivered through cesarean section could be attributed in part to their vulnerability to short interpregnancy intervals-related complications such as uterine rupture. 51 Moreover, previous studies have linked the mode of delivery to contraceptive use, 52 which is also found to be associated with short interpregnancy intervals. 53 , 54 Nakiwunga et al 52 noted that women who had cesarean delivery were more likely to initiate contraceptive use than their vaginal delivery counterparts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The higher awareness of women who delivered through cesarean section could be attributed in part to their vulnerability to short interpregnancy intervals-related complications such as uterine rupture. 51 Moreover, previous studies have linked the mode of delivery to contraceptive use, 52 which is also found to be associated with short interpregnancy intervals. 53 , 54 Nakiwunga et al 52 noted that women who had cesarean delivery were more likely to initiate contraceptive use than their vaginal delivery counterparts.…”
Section: Discussionmentioning
confidence: 99%
“… 51 Moreover, previous studies have linked the mode of delivery to contraceptive use, 52 which is also found to be associated with short interpregnancy intervals. 53 , 54 Nakiwunga et al 52 noted that women who had cesarean delivery were more likely to initiate contraceptive use than their vaginal delivery counterparts. Also, lower probabilities of short interpregnancy intervals were found to be associated with both initiation of immediate postpartum and interval long-acting reversible contraception.…”
Section: Discussionmentioning
confidence: 99%
“…Among the contraception users, 70% had four or more than four antenatal visits, whereas only 7.9 % had four and more than four antenatal visits in non-users. Women who had caesarean delivery were 2.6 times more likely to accept and use postpartum contraception than those who had vaginal delivery [ 16 ]. This is contradictory to our study in which 60% of the contraception users had a vaginal delivery.…”
Section: Discussionmentioning
confidence: 99%